(untitled) (Palíndromo, 2019)
Based on Walter Benjamin’s collec-tor’s concept (in “O Colecionador”, in the book Passagens, Editora UFMG, 2009) and in the proposition of Márcio Selig-mann-Silva regarding the act of anar-chiving to recollect, this article analyzes the work Desvio para o Vermelho [Red Shift] (1967-1984) by Cildo Meireles. By using the method of archiving in the for-mation of the collection that constitutes the work, the artist assumed the condi-tion of a type of collector. Thus, this ar-ticle investigates the attempts of Cildo Meireles to reorganise the world as from the different versions of the work.